«THE SILK ROAD ECONOMIC BELT»: DEVELOPMENT TENDENCIES IN THE INTERNATIONAL ECONOMIC AND LAW SYSTEMS - Y. V. Mishalchenko; T. I. Yuyukina (Дискурс, 2016)
The form of international integration - free trade zones - is being studied in the article. The preconditions which had contributed to the formation of the free trade Russian-Chinese zone in the city Heihe and development of cross-border economic cooperation are explored. As additional barriers to trade the issue of sanctions which predetermine the «eastern vector» of the economic development for Russia is analyzed. According to the authors, «The Silk Road Economic Belt» and its integral part - the transport corridor «Western Europe - Western China» contribute to the development and diversification of trade between Russia and China.